2015
DOI: 10.1002/qre.1939
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Multivariate Process Capability Indices Under Normal and Non‐Normal Distributions

Abstract: In the context of process capability analysis, the results of most processes are dominated by two or even more quality characteristics, so that the assessment of process capability requires that all of them are considered simultaneously. In recent years, many researchers have developed different alternatives of multivariate capability indices using different approaches of construction.In this paper, four of them are compared through the study of their ability to correctly distinguish capable processes from inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Table presents the probabilities of correctly identifying the state of the process, computed considering the value Φ p ; 0.0027 = 0.9973 ∀ p = 2, 3, 5 as the cutoff point. In the study of sensitivity and specificity carried out by Dianda et al , the index Mp 2 was found specific but not always sensitive, unless the anomaly in the process is very noticeable. When the index is computed from sampling information, the true value of the index is underestimated and so the index losses specificity.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Table presents the probabilities of correctly identifying the state of the process, computed considering the value Φ p ; 0.0027 = 0.9973 ∀ p = 2, 3, 5 as the cutoff point. In the study of sensitivity and specificity carried out by Dianda et al , the index Mp 2 was found specific but not always sensitive, unless the anomaly in the process is very noticeable. When the index is computed from sampling information, the true value of the index is underestimated and so the index losses specificity.…”
Section: Resultsmentioning
confidence: 94%
“…Specificity of this index could be affected because of the bias of its estimator. However, the ability of the estimator to correctly detect processes that meet specifications is not affected as the index is overvalued under this type of heavy‐tailed distributions . The magnitudes of the bias are not great enough to cancel out the overvaluation that the departure from normality causes in the index.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we have seen, authors that suggest using the PCA method to transform the original variance-covariance matrices, which describe the original PR, into a diagonal and uncorrelated-matrix are dealing with eliminating the correlation between the measured product characteristics. With this approach, the whole problem is moved to a new system of coordinate axes dened by the eigenvectors [70]. Once the product characteristics are uncorrelated, these authors suggest combining univariate PCIs to calculate the capability of each direction described by each eigenvector.…”
Section: Discussion: Multivariate Pcismentioning
confidence: 99%